The 'EMIRE' large rainfall simulator: design and field testing - Esteves, Michel; Planchon, Olivier; Lapetite, Jean Marc; Silvera, Norbert; Cadet, Patrice (Earth surface processes and landforms, 2000)
A rainfall simulator for 5 ×10 m plots was designed and tested within the EMIRE (Etude et Modélisation de l'Infiltration, du Ruissellement et de l'Erosion) program. The simulator is intended to be used in the field and to reproduce natural tropical rain storms. The simulator is composed of fixed stand pipes. The nozzle (Spraying Systems Co. 1H106SQ) mounted on the top of the pipes sprays square areas. At a water pressure of 41·18 kPa the mean drop diameter is 2·4 mm and the calculated kinetic energy 23·5 J m−2 mm−1. The pipes are located at the corners of a 5·5 × 5·5 m square grid. The rainfall intensity is constant (65 mm h−1) and spatially uniform (Christiansen's coefficient of uniformity is 78 to 92 per cent) over the plot. Repeatability of application rate and spatial variability of rainfall intensities were tested by analysing (1) variations in intensity for different experiments on the same plot, and (2) variations in intensity between different plots. The study is based on data collected during nine field rainfall simulation experiments. Three replications of the same rain were applied on three 50 m2 plots. The results show good performance in all cases. The values of the mean rainfall intensities and coefficient of uniformity obtained from field data agreed with the laboratory values. The performance of this simulator is comparable to others described in the literature. Copyright © 2000 John Wiley & Sons, Ltd.